If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Z + -4x = 2y Solving Z + -4x = 2y Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '4x' to each side of the equation. Z + -4x + 4x = 4x + 2y Combine like terms: -4x + 4x = 0 Z + 0 = 4x + 2y Z = 4x + 2y Simplifying Z = 4x + 2y
| y^3+2x=x-1 | | (8+2i)(5-9i)= | | -36+4x=12 | | 2x+4y-1=3+y | | 8-8x20/20 | | f(x+8)=2x-4 | | x^2+lnx-1=0 | | 15+5x=40 | | (7/(3a))/(2/5) | | 2x^-5/3y^0 | | (7/(3a))/(2.5) | | x=1/50 | | -(-8)/(-8)-3 | | 2/5x30=-50 | | 2x=1/25 | | 8x+3=3x+9 | | 3(2x+8)=15 | | cosx/3=0 | | -3x+14=23 | | R=-4x-9z+5z-9x+3x-8z | | x*2=1/25 | | 9y^2+1=6x | | (10x^6)(5x^2)= | | A=-7x+3y-7y+8x-6x+9y | | 15x^2+x^3=0 | | 0.5x^3-1.5x^2+4=0 | | V=-9y+7y-5+4 | | x-150000=1.4x | | X=582 | | .006*x=12 | | 9x+1-9x=72 | | 2*ln^2(2)=x |